Sinai in Arabic literature from the Beginning of the 20th century up to the end of 2012: a Bibliometric study - Maher Masoud (Cybrarians Journal, 2020)
The study aims to address the topic of "Sinai in Arabic literature between 1900-2012” to identify the diversity of subjective and qualitative and formal as well as uncover areas of strength and weakness in this literature to make use of the strengths points and work on areas of weakness to get over them.